Soil protection in the period of climate change - Vovk, Ana (Journal for Geography, 2022)
Soil protection is a relevant topic in times of drought, floods and fires. In view of increasingly difficult growing conditions, soil protection systems are gaining in natural approaches. In 2022, the global movement Save the Soil took place, during which active encouragement for preparation of Soil Strategy was given to various organizations and experts. This article highlights soil protection processes, which are present in Slovenia. The emphasis is on regenerative approaches, which are also supported by the European Commission as part of the Green Deal. Experience shows that such approaches are in the initial phase and that they are proving to be necessary for adaptation to climate change.
Keywords: climate change; organic matter; regeneration agriculture; revitalisation; soil